2015
DOI: 10.1073/pnas.1423808112
|View full text |Cite
|
Sign up to set email alerts
|

Environmental CO 2 inhibits Caenorhabditis elegans egg-laying by modulating olfactory neurons and evokes widespread changes in neural activity

Abstract: Carbon dioxide (CO 2 ) gradients are ubiquitous and provide animals with information about their environment, such as the potential presence of prey or predators. The nematode Caenorhabditis elegans avoids elevated CO 2 , and previous work identified three neuron pairs called "BAG," "AFD," and "ASE" that respond to CO 2 stimuli. Using in vivo Ca 2+ imaging and behavioral analysis, we show that C. elegans can detect CO 2 independently of these sensory pathways. Many of the C. elegans sensory neurons we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 80 publications
(109 reference statements)
0
54
0
Order By: Relevance
“…Odorants and pheromones are detected by large families of seven-transmembrane domain G protein-coupled receptors (GPCRs) [68, 72], while the gustatory response requires receptor guanylate cyclases (rGCs) [73]. CO 2 detection is mediated in part by the rGC GCY-9 [7476]; however, GCY-9-independent mechanisms of CO 2 detection appear to operate in some sensory neurons but have not yet been characterized [77, 78]. O 2 detection is mediated by soluble guanylate cyclases and globins [7981].…”
Section: The Neural Basis Of Host-seeking Behaviormentioning
confidence: 99%
“…Odorants and pheromones are detected by large families of seven-transmembrane domain G protein-coupled receptors (GPCRs) [68, 72], while the gustatory response requires receptor guanylate cyclases (rGCs) [73]. CO 2 detection is mediated in part by the rGC GCY-9 [7476]; however, GCY-9-independent mechanisms of CO 2 detection appear to operate in some sensory neurons but have not yet been characterized [77, 78]. O 2 detection is mediated by soluble guanylate cyclases and globins [7981].…”
Section: The Neural Basis Of Host-seeking Behaviormentioning
confidence: 99%
“…We studied how prior O 2 experience alters CO 2 responses because the special relationship between these gases has ecological implications. However, C. elegans has many CO 2 -responsive neurons, complicating analysis of how persistent differences in RMG activity alter the CO 2 circuits (38,45,46). Several studies have reported differences in the sensory responses of N2 and npr-1 mutants that are associated with altered RMG function (35,36,47,48).…”
mentioning
confidence: 99%
“…elegans [86][87][88][89][90], we speculate that AdCR may represent a homeostatic mechanism to maintain sensory cilia function and reproductive fitness under specific conditions. Similar mechanisms may operate in other organisms to maintain cilia function in IFT mutants.…”
Section: Discussionmentioning
confidence: 91%